2022
DOI: 10.1111/apps.12366
|View full text |Cite
|
Sign up to set email alerts
|

Staying focused when nobody is watching: Self‐regulatory strategies to reduce mind wandering during self‐directed learning

Abstract: Mind wandering, the direction of attention away from a primary task, has the potential to interfere with learning, especially in increasingly common self-directed learning environments. By integrating self-regulated learning and mind wandering theories, we developed three interventions to encourage on-task focus in a selfdirected training environment. We tested these selfregulation interventions in two experiments: a field study with working adults (Study 1, N = 133) and a lab study with college students (Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In the interviews, a large percentage of the students believed they had low self-discipline. Learning can be affected by mind wandering and attention distracted from a task, especially in increasing online learning environments (Randall et al, 2022 ). Your brain automatically identifies the home as a place to rest when you take online classes at home, making it difficult to focus on and control your learning .…”
Section: Model Interpretationmentioning
confidence: 99%
“…In the interviews, a large percentage of the students believed they had low self-discipline. Learning can be affected by mind wandering and attention distracted from a task, especially in increasing online learning environments (Randall et al, 2022 ). Your brain automatically identifies the home as a place to rest when you take online classes at home, making it difficult to focus on and control your learning .…”
Section: Model Interpretationmentioning
confidence: 99%
“…In this study, we considered the role of mindfulness ‐ individuals' capability to anchor their attention to and awareness on the present without instant and subjective judgment (Brown et al, 2007). Prior studies have found that mindfulness increases individuals' abilities to cope with various competing demands in various domains by promoting attention and emotion regulation (e.g., Allen et al, 2015; Park & Nam, 2020; Randall et al, 2022). Specifically, mindfulness directs individuals' abilities to perceive surroundings and observe their mental patterns keenly, enabling them to discern the most prominent demand at present (Zheng et al, 2022) and thus maintain focused attention when playing a specific role (i.e., the current role, such as a family role).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%